Jono Rėzos 1625 m. psalmyno kirčiavimas - Palionis, Jonas; Strockis, Mindaugas (Baltistica, 2005)
THE ACCENTUATION OF JONAS RĖZA’S PSALTER OF 1625Accent marks in Lithuanian writings occasionally appear in the Catechism (1547) and the Hymnal (1570) of Martynas Mažvydas. A more advanced system can be observed in the Gospels and Epistles of Baltramiejus Vilentas (1579), who used acute, grave, angled circumflex, and a tilde-shaped circumflex. The latter was used exclusively in genitive plural ending -ũ, which practice seems to be modeled on the Greek circumflex as in ϑεω̃ν, and Latin nasalization tilde as in deorũ, as well as the humanist Latin distinctive circumflex as in deûm (=-orum).The accent marks used by Rėza in his 1625 Psalter are acute, grave, angled circumflex and dot accent. The inventor of the last of these marks was apparently Rėza himself.The circumflex in Rėza’s Psalter has two different functions, that of signifying the actual word stress and that of distinguishing otherwise homonymous word forms. In the latter case it does not necessarily occur on the actually stressed syllable. Most often the circumflex in this capacity is employed in the genitive plural ending -û (like in Latin -ûm).It seems likely that Rėza did not have a conscious intention of conveying actual syllabic intonations, as is shown by the inconsistencies in his use of accent marks. A special case seems to be the circumflex on ê: here the accent sign appears to have an additional phonetic meaning – that is, Rėza’s ê usually corresponds to the long narrow vowel (which in modern Lithuanian is written ė). This practice was apparently based on intuitive comparison of the humanist Latin orthography (such as legere versus legêre) with Lithuanian phonetics.The dot accent is used in the inessive (locative) singular ending -ė (-e in modern orthography), sometimes also in the instrumental singular, and rarely in the inessive plural. Like circumflex, the dot accent does not always coincide with the actually stressed syllable. The sign was most likely modeled on the humanist Latin circumflex distinguishing the ablative singular ending -â, as suggested in Daniel Klein’s Grammatica Litvanica.The language of Rėza’s Psalter is closest to the West High Prussian dialect of Lithuanian, so the actual word accent in the Psalter is in most cases identical to that of standard modern Lithuanian. Certain differences (apart from the purely distinctive use of accent marks) can be explained as archaisms, or the influence of non-western dialects of Lithuania Minor, or as typesetter’s errors.Rėza’s system of marking accents in writing is notably close to that of Daniel Klein. Apparently Klein was familiar with Rėza’s work and adopted some of his practices; but, being a man of greater linguistic ability, he had a better grasp of the actual syllabic intonations of Lithuanian. Many of the similarities between Rėza’s and Klein’s accent notation however can be simply explained: both authors had based their systems on the Latin spelling habits and the Greek accentuation.It can also be observed that the emergence of accent marks in Lithuanian is roughly contemporary with the rise of distinctive diacritics in the Latin orthography: accent marks are rare and occasional in Mažvydas (as well as in his Latin writings), but towards the end of the 16th and in the 17th century the accents become much more regular and frequent.
Keywords: senieji raštai; kirčiavimas; J. Rėza